A combination of friedel-crafts and lawesson reactions to 5-substituted-2,2´-bithiophenes - Raposo, M. Manuela M. (2001)
Gama-Keto esters (2) derivatives of thiophene were obtained from hemi-succinic esters and transformed to the corresponding amides (4). Lawesson´s treatment of 2 and 4 gave the corresponding bithiophenes (5) with alkoxy or amino substituents.